Analisis Transfer Fee di dalam Sistem Transfer Pemain Terhadap Industri Sepak Bola Indonesia - Rizky Fatmala (Jurnal Indonesia Sosial Sains, 2023)
This paper wants to analyze the transfer fee mechanism for Indonesian football players in the system established by FIFA which is experiencing rapid progress. Like a business entity in general, a football club needs resources to carry out its activities. Player transfers are a very important aspect of the football business. The Federation Internationale the Football Association (FIFA) is the governing body of football in which it takes a global role in the relationship between sport and politics. Therefore, it is important to see how the transfer fee mechanism in the system established by FIFA affects the football industry in Indonesia. The paradigm used in this paper is the Liberalist paradigm, where individual freedom in liberalism helps society in developing ideas, and Neoliberalism, which is characterized by ideas that emphasize deregulation or market regulation, the non-opening of state-owned enterprises (SOEs), limited government interference, and a more open international market.